ANALISIS HUKUM EKONOMI SYARIAH TERHADAP PERAN BANK ADMINISTRATOR RDN (REKENING DANA NASABAH) KONVENSIONAL DI PT. INDOPREMIER SEKURITAS - Fiska Nurhayati; Muhammad Hasanuddin; Siti Nur Fatoni (Al-Muamalat: Jurnal Ekonomi Syariah, 2020)
RDN Bank Administrators are investors' deposit funds, at this time in Indonesia there have been three RDN Sharia Bank Administrators. This research is motivated by regulations regarding the prohibition of using Ribawi financial services in investments in the Islamic capital market. All instruments and mechanisms in the Islamic capital market must be in accordance with Islamic principles. There are Securities Companies that use conventional RDN Administaror Banks in sharia securities sale and purchase transactions. Securities companies that provide SOTS (Sharia Online Trading System) facilities should have all the processes adjusted to the provisions issued by the regulator. This study aims to determine the legal position of conventional RDN (Customer Fund Account) storage according to Sharia Economic Law in Indonesia. The method used in this research is juridical-normative. Based on the results of the study, it can be concluded that the activities of Islamic capital market investment in PT. Indo Premier Sekuritas has used SOTS (Sharia Online Trading System) as well as in its mechanism PT.Indo Premier Sekuritas has separated from non-halal effects. However, it becomes an obstacle when investors move their securities accounts from regular to SOTS, RDN banks that are used continue to use conventional. The legal status of depositing Conventional RDN (Customer Fund Account) according to the juridical aspects of Sharia Economic Law is not in accordance with sharia principles in the capital market, and has violated POJK No. 15 of 2015 Article 2 Paragraph 1 concerning Application of Sharia Principles in the Capital Market.